Enantioselective N-Alkylation of Nitroindoles under Phase-Transfer Catalysis - Trubitsõn, Dmitri; Martõnova, Jevgenija; Erkman, Kristin; Metsala, Andrus; Saame, Jaan; Kõster, Kristjan; Järving, Ivar; Leito, Ivo; Kanger, Tõnis (Synthesis, 2020)
An asymmetric phase-transfer-catalyzed N-alkylation of substituted indoles with various Michael acceptors was studied. Acidities of nitroindoles were determined in acetonitrile by UV-Vis spectrophotometric titration. There was essentially no correlation between acidity and reactivity in the aza-Michael reaction. The position of the nitro group on the indole ring was essential to control the stereoselectivity of the reaction. Michael adducts were obtained in high yields and moderate enantioselectivities in the reaction between 4-nitroindole and various Michael acceptors in the presence of cinchona alkaloid based phase-transfer catalysts. In addition to outlining the scope and limitations of the method, the geometries of the transition states of the reaction were calculated.
Keywords: asymmetric catalysis; heterocycles; Michael addition; organocatalysis; phase-transfer catalysis